Youth bulges, insurrections, and politico-economic institutions - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2014)
We develop a simple model of an insurrection market based on a kleptocratic politico-economic institutional setting, within which a certain government elite holds both all central government position and all productive assets. The kleptocratic setting provokes the appearance of insurrection entrepreneurs that are called the revolutionary elite and that aim at redistributing wealth away from the government elite. To that end, the revolutionary elite hires insurrection activists and compensates them in cash or in kind. We integrate the youth bulge measured by the relative youth cohort size into the insurrection market by defining certain youth-specific characteristics that influence relative productivities on the insurrection market as compared to an official labor market. We find that, apart from certain spontaneous outbreaks of violence or riots, youth bulges alone are not a good predictor for political violence. Moreover, deliberate insurrection activities that aim at changing political and economic power positions are affected by youth bulges only when related to certain politico-economic institutional settings, from which kleptocracies may be the most vulnerable.
Keywords: H56; J10; J22; P16; 330; youth bulges; insurrections; political economy of revolutions